ChemInform Abstract: Synthesis, Structure and Total Conductivity of A‐Site Doped LaTiO3‐δ Perovskites. Issue 12 (March 2015) - Bradha, M.; Hussain, S.; Chakravarty, Sujay; Amarendra, G.; Ashok, Anuradha
Abstract LaTiO3‐δ and La0.8A0.2TiO3‐δ (A: Ba, Sr, Ca) are prepared by sol‐gel processing of La(NO3)3, alkali acetates, and (Pr‐O)4Ti using citric acid and PEG (60 °C, 8 h).